Peran E-WoM, E-Reputation, dan Dalam Membangun Destination Image Serta Meningkatkan Intention To Visit Ke Kepulauan Seribu - Dicky Gilang Ramadhan; Dimas Angga Negoro (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2026)
This study aims to analyze the role of Electronic Word of Mouth (E-WOM) and Electronic Reputation (E-Reputation) in building Destination Image and their influence on Intention to Visit Kepulauan Seribu. This research employs a quantitative approach using a survey method involving 180 respondents from the Jakarta metropolitan area and is analyzed using Structural Equation Modeling (SEM). The results indicate that E-WOM has a positive and significant effect on E-Reputation and Destination Image, while E-Reputation also has a positive and significant influence on Destination Image. Furthermore, Destination Image is proven to have a positive and significant effect on Intention to Visit. These findings suggest that positive information disseminated through digital media and a strong online reputation play a crucial role in shaping destination image, which ultimately encourages tourists’ intention to visit. This study provides managerial implications for destination managers to strategically manage E-WOM and E-Reputation in order to enhance destination image and increase tourists’ visit intention to Kepulauan Seribu. It is hoped that this research can provide a major contribution to the world of tourism, as well as important information on the influence of positive information, the reputation of a place, and customer satisfaction on the intention to visit a destination.